Psycholinguistic models of speech development and their application to clinical practice. - Baker, Elise; Croot, Karen; McLeod, Sharynne (Journal of Speech, Language & Hearing Research, 2001)
This article presents on introduction to psycholinguistic models of speech development. Two specific types of models are addressed: box-and-arrow models and connectionist or neural network models. We review some historical and some current models and discuss recent applications of such models to the management of speech impairment in children. We suggest that there are two ways in which a psycholinguistic approach can influence clinical practice: by directly supplementing a speech-language pathologist's repertoire of assessment and treatment approaches and by offering a new way to conceptualize speech impairment in children. Reprinted by permission of the publisher.